Student Profile-Based Curriculum Design for Fostering Character Education in Secondary Schools - Handayani, Assyifa; Dwi Safitri, Ikromatul Fathiyah (Jayapangus Press, 2025)
This study analyzes the implementation of a Pancasila Student Profile-based curriculum design at SMP Islam Al Azhar BSD using a qualitative approach. Data were collected through observations, interviews, and document analysis. The findings reveal that the school’s curriculum is designed by considering scope, sequence, continuity, integration, articulation, and balance. It is developed with a focus on balancing academic aspects, spiritual values, and students’ social development. Character strengthening is carried out through the integration of intracurricural, co-curricular, and extracurricular activities. The curriculum encompasses programs, planning, subject content, and learning experiences that align with the school’s vision, mission, and goals. The strategic implications of this research support curriculum development at SMP Islam Al Azhar BSD and can serve as a reference for other educational institutions in integrating Pancasila values into learning.